Science-policy dialogue in the eastern Nile Basin to enhance synergies across the water, food, energy and ecosystems - Taye, Meron Teferi; Ebrahim, Girma; Seid, Abdulkarim (International Water Management Institute, 2025)
In the eastern Nile Basin, researchers and policymakers are coming together to put solutions into practice at the intersection of water, food, energy and ecosystems.